A Simple and Powerful tert-Butylation of Carboxylic Acids and Alcohols - Ogasa, Chie; Kayano, Kimika; Namba, Kosuke (Synlett, 2023)
A simple and safe tert-butylation reaction was developed. Treatment of various free amino acids with 1.1 equivalents of bis(trifluoromethanesulfonyl)imide in tert-butyl acetate directly afforded tert-butyl esters with free amino groups quickly and in good yields. In addition, various carboxylic acids and alcohols without amino groups were converted into tert-butyl esters and ethers, respectively, in high yields in the presence of small catalytic amounts of bis(trifluoromethanesulfonyl)imide. All tert-butylation reactions of free amino acids, carboxylic acids, and alcohols proceeded much faster and in higher yields compared with conventional methods.
Keywords: tert-butylation; amino acids; tert-butyl esters; tert-butyl ethers; bis(trifluoromethanesulfonyl)imide